Analytical solutions of photo-thermo-elastic waves in a non-homogenous semiconducting material - Hobiny, Aatef; Abbas, Ibrahim A. (Results in physics, 2018)
In the present paper, the wave propagation on non-homogenous semiconductor through photo-thermal process has been studied by using the theory of coupled plasma and thermoelastic wave. Without neglecting the coupling between the plasma and thermoelastic wave that photo-generated through intensity modulated laser beam and tightly focused, a semiconducting isotropic elastic medium has non-homogeneity in thermal and elastic properties are considered. The analytical solutions in the domain of Laplace by the eigenvalues approach were observed through the transform techniques of Laplace. Silicon-like semiconductor was used to achieve the numerical computations.